SLEEP OPTIMIZATION FOR RECOVERY, HEALTH AND PERFORMANCE IN ATHLETES - A LITERATURE REVIEW - Paulina Bernecka,; Oliwia Sójkowska-Sławińska,; Anna Leśniewska,; Patryk Macuk,; Michał Gniedziejko,; Jakub Roszak,; Bartosz Michał Skorupski,; Natalia Strumnik,; Agata Firkowska, (International Journal of Innovative Technologies in Social Science, 2025)
Sleep plays an essential role in physical recovery, cognitive readiness and overall performance in athletes. However, this particular group frequently experiences sleep architecture disruption. Problems may include shortened, irregular and disturbed sleep due to late training sessions, competition stress, travel across time zones and simultaneous demands of academics and sport. This narrative review integrates findings from research conducted between 2020 and 2025 examining sleep duration, sleep quality and evidence-based strategies to enhance sleep among athletes. In the article, we try to identify major influences on sleep quality, ranging from behavioral factors (evening screen use, consumption of caffeine and meal timing) to environmental factors (light, noise, temperature) and biological rhythms (chronotype, social jetlag and delayed bedtimes). We analyze current approaches to monitoring sleep pointing out strengths and limitations of technologies such as polysomnography, actigraphy, EEG head bands, wearables and subjective questionnaires (PSQI and ESS). Focusing on recovery, in the article we discuss objective markers of sleep including HRV (heart rate variability), resting heart rate, sleep latency. We describe effective sleep-optimization strategies for athletes and other groups vulnerable to sleep deprivation. The methods include light-based protocols, environmental adjustments, nutritional timing, supplementation (melatonin, tryptophan) and training and recovery scheduling. Overall, the findings emphasize that sleep is a critical and modifiable determinant of athletic success. There is a complex and integrated relationship between sleep, recovery and daily performance that can be enhanced and cared for by sleep hygiene practices, scheduling training according to individual chronotypes and using multimodal physiological monitoring.